Corporate governance reforms in continental Europe - Enriques, L; Volpin, PF (American Economic Association, 2007)
The fundamental problem of corporate governance in the United States is to alleviate the conflict of interest between dispersed small shareowners and powerful controlling managers. The fundamental corporate governance in continental Europe and in most of the rest of the world is different. There, few listed companies are widely held. Instead, the typical firm in stock exchanges around the world has a dominant shareholder, usually an individual or a family, who controls the majority of the votes. In this essay, we begin by describing the differences in the ownership structure of companies in the three main economies of continental Europe -- Germany, France, and Italy -- with comparisons to the United States and the United Kingdom. We next summarize the corporate governance issues that arise in firms with a dominant shareholder. We take a look at a major European corporate scandal, Parmalat, as an extreme example of investor expropriation in a family-controlled corporation. We outline the legal tools that can be used to tackle abuses by controlling shareholders. Finally, we describe the corporate governance reforms enacted by France, Germany, and Italy between 1991 and 2005 and assess the way in which investor protection in the three countries has changed.